Membangun Empati Dan Kepedulian Sosial Melalui Pendidikan Multikultural Di Kelas Sekolah Dasar - Sulfani Sulfani; Waode Arifatun; Ekson Ekson (Prodi PGSD Unsultra, 2023)
This study aims to explore the role of multicultural education in building empathy and social awareness of elementary school students. This study reviews various literatures to understand how multicultural approaches can be applied in the curriculum and learning activities. The findings show that multicultural education based on the introduction of diversity, inclusive values, and collaborative activities can improve students' social sensitivity and empathy skills.